GAP ANALISIS PENERAPAN SMART MOBILITY DI SEKITAR KAWASAN MANDALIKA - Reza Yoga Anindhita; Ramadhan Dwi Prasetyo; Aprianto, Rizal (Jurusan Teknik Perencanaan Wilayah dan Kota, Fakultas Sains dan Teknologi, Universitas Islam Negeri Alauddin Makassar, 2024)
The presence of the Mandalika Tourism Area has become one of the driving factors for the selection of Mataram City, North Lombok Regency, East Lombok Regency, West Lombok Regency, and Central Lombok Regency as cities/regencies participating in the